Balancing continuity and adjustments in Brazil’s foreign policy towards China: a comparative approach between Bolsonaro and Lula’s third term - Rubiolo, María Florencia (2024)
Bolsonaro’s foreign policy, characterized by a staunchly conservative identity aligned with far-right populist ideologies, emphasized anti-globalism, nationalism, and adversarial narratives. His administration fostered close ties with the Trump Administration, influencing Brazil’s shift away from emerging countries and international blocs. This pivot tested Brazil´s previously strong relationship with China, leading to stagnation in diplomatic and political relations, contrasting sharply with theproactive approaches of Bolsonaro´s predecessors.With Lula da Silva´s return to the presidency in 2023, Brazilian foreign policy underwent significant revision during his first hundred days. Lula aimed to restore key elements of his earlier foreign policy, emphasizing South-South cooperation, revitalizing the BRICS, and redefining Brazil’s international agenda amid the ongoing Ukraine conflict. This reorientation notably impacted Brazil-China relations. This paper provides an in-depth analysis of Jair Bolsonaro’s foreign policy towards China from 2018 to 2022 and examines the first year of Lula da Silva’s administration in 2023. It explores the diplomatic and economic dimensions of their respective approaches towards China, highlighting both changes and continuities. The main argument posits that during Bolsonaro’s tenure, Brazil’s relations with China underwent political and diplomatic adjustments in line with the administration’s conservative foreign policy narrative. Despite this, China retained a crucial role in Brazil’s economic agenda. Following Lula’s return to power in 2023, diplomatic initiatives towards China were rejuvenated, reflecting a political rapprochement with Beijing. This shift materialized through high-level official engagements and continued robust economic ties, illustrating a restored bilateral and multilateral relationship.